ANALISIS PENERAPAN LIMA PRINSIP ETIKA BISNIS PADA WARUNG SEBLAK 910 CABANG DEMANG LEBAR DAUN KOTA PALEMBANG: ANALISIS PENERAPAN LIMA PRINSIP ETIKA BISNIS PADA WARUNG SEBLAK 910 CABANG DEMANG LEBAR DAUN KOTA PALEMBANG - Ulandari, Suci; Septiani, Debi; Andi, Muhammad Distian (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2023)
This research aims to determine the influence of product quality and brand image on the feasibility of a business. The importance of understanding the factors that influence brand loyalty to a product. In this research, business ethics has been applied to brand image. This scientific journal reviewed several previous studies showing that Brand image, product quality, customer satisfaction and customer trust influence customer loyalty in brand image. By using quantitative methods, therefore, this research aims to determine the influence of product quality and brand image on customer satisfaction, with the increasingly developing brand image which influences product quality, companies can maintain product quality and improve the quality of brand image and how consumers apply and manage it. satisfaction with the brand image used by consumers.